2019
DOI: 10.1002/jmri.26847
|View full text |Cite
|
Sign up to set email alerts
|

Clinical assessment of aortic valve stenosis: Comparison between 4D flow MRI and transthoracic echocardiography

Abstract: Background The prevalence of valvular aortic stenosis (AS) increases as the population ages. Echocardiographic measurements of peak jet velocity (Vpeak), mean pressure gradient (Pmean), and aortic valve area (AVA) determine AS severity and play a pivotal role in the stratification towards valvular replacement. A multimodality imaging approach might be needed in cases of uncertainty about the actual severity of the stenosis. Purpose To compare four‐dimensional phase‐contrast magnetic resonance (4D PC‐MR), two‐d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…The 4D‐flow technique is particularly useful to assess CHD, as it provides more comprehensive flow data in a wide range of cardiac pathologies through the acquisition of a single 3D volume . Some authors have also compared 4D‐flow MRI to echocardiography to measure flow volumes at the carotid bifurcation and in aortic valve stenosis, reporting good correlation between the two techniques, and demonstrating the potential utility of 4D‐flow MRI to provide greater concordance or flow parameters to the measurements obtained by echocardiography.…”
Section: Discussionmentioning
confidence: 90%
“…The 4D‐flow technique is particularly useful to assess CHD, as it provides more comprehensive flow data in a wide range of cardiac pathologies through the acquisition of a single 3D volume . Some authors have also compared 4D‐flow MRI to echocardiography to measure flow volumes at the carotid bifurcation and in aortic valve stenosis, reporting good correlation between the two techniques, and demonstrating the potential utility of 4D‐flow MRI to provide greater concordance or flow parameters to the measurements obtained by echocardiography.…”
Section: Discussionmentioning
confidence: 90%
“…Studies with bicuspid aortic valve patients revealed peak velocities of up to 2.3 m/s, 34 whereas much higher flow velocities of up to 4.7m/s have been reported in aortic valve stenosis patients. 35,36 Furthermore, WSS has been evaluated in the context of these diseases 31,32 because it has a direct impact on cell function and influences aortic wall remodeling. Moreover, some gradient systems today are more performant than the system used here (AS095DS, Siemens Healthineers), which in principle could be used to decrease gradient timings and thus the magnitude of the displacement artifacts.…”
Section: Discussionmentioning
confidence: 99%
“…However, especially in pathologies, the quantification of hemodynamic parameters is of high interest. Studies with bicuspid aortic valve patients revealed peak velocities of up to 2.3 m/s, 34 whereas much higher flow velocities of up to 4.7m/s have been reported in aortic valve stenosis patients 35,36 . Furthermore, WSS has been evaluated in the context of these diseases 31,32 because it has a direct impact on cell function and influences aortic wall remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…Pronounced flow eccentricity is associated with greater differences in peak jet velocity between transthoracic echocardiography and 4D flow MRI. 30 In healthy volunteers and patients with AS, 4D flow MRI allows for improved flow quantification relative to transthoracic echocardiography. [30][31][32] Research has also demonstrated that helical blood flow, vortical blood flow, and blood eccentricity assessed using 4D flow MRI become stronger as the disease progresses in patients with AS.…”
Section: Clinical Application For Aortic Valvular Diseasementioning
confidence: 99%